(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This study investigates the cross-cultural pragmatic contrasts in speech acts used in English and Uzbek languages. In this paper, the ways of sociocultural values in English-speaking contexts and collectivism in Uzbek society shaping spoken language through exploring demands, apologies, compliments, refusals, and expressions of gratitude. Based on theories of pragmatics and intercultural reationships, this comparative study emphasizes the significance of understanding social rules of language and knowing how to use the correct words or grammar to express intentions in language teaching and intercultural competence development.